Mining Africa. Law, Environment, Society and Politics in Historical and Multidisciplinary Perspectives : Law, Environment, Society and Politics in Historical and Multidisciplinary Perspectives - Warikandwa, Tapiwa V.; Nhemachena, Artwell (Book collections on Project MUSE., 2017)
This book is a pacesetter in matters of mining and the environment in Africa from multidisciplinary and spatio-temporal perspectives. The book approaches mining from the perspectives of law, politics, archaeology, anthropology, African studies, geography, human ecology, sociology, history, economics and development. It interrogates mining and environment from the perspectives of customary law as well as from the perspectives of Euro-modern laws. In this sense, the book straddles precolonial, colonial and postcolonial mining and environmental perspectives. In all this, it maintains a Pan-Africanist perspective that also speaks to contemporary debates on African Renaissance and to the unity of Africa. From scrutinising the lived realities of African miners who are often insensitively and unjustly addressed as "illegal" miners, the book also interrogates transnational mining corporations; matters of corporate social responsibility as well as matters of tax evasions by transnational corporations whose commitment to accountability to African governments is questioned. With both theoretical chapters and chapter based on empirical studies on mining and the environment across the African continent, the book provides a much needed holistic, one stop shop for scholars, activists, researchers and policy makers who need a comprehensive treatise on African mining and the environment. The book comes at the right time when matters of African mining and environment are increasingly coming to the fore in the light of discourses about the new 21st century scramble for African resources, in which big transnational corporations and nations are jostling to suck Africa dry in their race to control planetary resources. It is a book that speaks to contemporary broader issues of (de-)coloniality and transformation of African minds and African environmental resources.